Descriptions of neurocranium morphology in 34 species of moray eels (Muraenidae) found in Taiwan - Ramos-Castro, Marites; Chen, Hong-Ming; Mao, Bo-Syun (Zootaxa, 2020)
Taiwan is one of the richest in the world in terms of eel fauna. In this study, we examined the osteological and morphological characteristics of eels in the family Muraenidae. Furthermore, we focused on the neurocranium of 34 muraenid species in the genera Echidna (2), Enchelycore (3), Gymnomuraena (1), Gymnothorax (25), Scuticaria (1), Strophidon (1), and Uropterygius (1), which are caught in Taiwanese waters. This paper shows the results of a comparative study on osteological characters of the neurocranium including the ratio of nine length characters and 20 diagnostic characters for 34 eel species in the family Muraenidae. The subfamily Uropterygiinae is distinguished from the subfamily Muraeninae in having the lowest value on the depth of mid pre-orbit due to the termination of the ethmoidal crest toward premaxilla. Moreover, aside from Gymnomuraena zebra, the species of subfamily Uropterygiinae have the lowest orbit length. These results in neurocranial comparative morphology between the species are consistent with their previous classification based on molecular results. These morphological and osteological characters may be valuable for taxonomic purposes and might be used as the basis for further studies on the status of genera in Muraenidae.